BEYOND SWEETNESS: EXPLORING SUBSTRATE INHIBITION IN SUGAR ALCOHOL OXIDATION - Latona , Oluwadayo Adesina; Olawale, Ifeoluwa Temitope (Global Journal of Chemistry, Biology and Physics (GJCBP), 2024)
Sugar alcohols, recognized as polyols, emerge as promising sugar substitutes due to their similar appearance and sweetness properties, despite being neither alcohols nor sugars in the traditional sense. This paper explores the distinctive characteristics of sugar alcohols, emphasizing their lower calorie content and reduced negative health impacts compared to conventional sugars. Unlike sugars, sugar alcohols exhibit limited absorption into the bloodstream, resulting in minimal effects on blood sugar levels and offering protection against tooth decay by resisting bacterial fermentation in the mouth. Studies indicate that sugar alcohols can contribute to health improvement, marking a departure from the potential adverse effects associated with regular sugars. The relative sweetness of specific sugar alcohols—sorbitol, mannitol, maltitol, erythritol, and lactitol—varies, with their taste perceived as considerably less sweet than traditional sugars, often accompanied by a minty or cool flavor. While previous research has reported the kinetics of sugar alcohols' reactions with various oxidizing agents, there remains a dearth of comprehensive studies on the oxidation of sugar alcohols compared to sugars. This paper addresses this research gap by providing insights into the kinetics and mechanism of the alkaline KMnO4 oxidation of two specific sugar alcohols, D-sorbitol and D-dulcitol. The investigation delves into the intricacies of this oxidation process, shedding light on the reactions that occur and the underlying mechanisms governing these transformations. By elucidating the kinetics and mechanisms involved, this study contributes valuable knowledge to the understanding of sugar alcohols' chemical behavior, offering potential applications in diverse fields, from health-conscious food production to eco-friendly chemical processes.